Family as a Context for Child Development: Mothers with the FMR1 Premutation and Their Children with Fragile X Syndrome - Bangert, Katherine; Moser, Carly; Friedman, Laura; Klusek, Jessica (Seminars in Speech and Language, 2021)
Fragile X syndrome (FXS) is a genetic disorder caused by changes of the FMR1 gene that is passed along among families. A range of developmental processes may be impacted with wide variation in abilities across individuals with FXS. Mothers of children with FXS are often carriers of a “premutation” expansion on the FMR1 gene, which is associated with its own clinical phenotype. These maternal features may increase individual and family vulnerabilities, including increased risk for depression and anxiety disorders and difficulties in social and cognitive ability. These characteristics may worsen with age, and potentially interact with a child's challenging behaviors and with family dynamics. Thus, families of children with FXS may experience unique challenges related to genetic risk, manifested across both children and parents, that should be considered in therapeutic planning to optimize outcomes for children and their families. In this article, we review core features of the FMR1 premutation as expressed in mothers and aspects of the family environment that interface with developmental outcomes of children with FXS. Recommendations for family-centered support services are discussed.
Keywords: fragile X premutation; fragile X syndrome; fragile X carriers; mother–child associations